Menstrual Cycle Determinants - Jawiah; Retno Dwi Lestari; Ratna Ningsih; Eva Susanti; Rehana (International Journal Scientific and Professional (IJ-ChiProf), 2022)
Adolescence is a transition from childhood to adulthood accompanied by biological, psychological, and sociological changes. One of the biological changes in adolescent girls is menstruation. Menstruation is a sign of femininity for women, but menstruation often experiences disorders, one of which is menstrual cycle disorders that are influenced by several factors. This study aims to look at the determinants associated with the menstrual cycle. Factors to be investigated are stress, Body Mass Index (BMI), and physical activity. This research was conducted at Madrasah Aliyah Ar-Rahman Palembang with a cross-sectional approach. The sampling technique used in this study is total sampling with 102 respondents, conducted in March 2020. The statistical test of this study uses Chi-square and multiple logistic regression. Bivariate analysis results show that there is a relationship between stress (p-value 0.000, OR = 7.879, BMI (p-value 0.008, OR = 3.321), and physical activity (p-value 0.006, OR = 3.525) with menstrual cycle. Results of multivariate analysis of stress variables (p-value 0.000, Exp (B) = 6.960) and physical activity (p-value 0.033, Exp (B) = 2.805) with the menstrual cycle so that the determinant of this research factor is stress.